Naringenin alters the pharmacokinetics of ranolazine in part through the inhibition of cytochrome P450 (3A4) and P-glycoprotein - Faisal Alotaibi (SpringerOpen, 2023)
Abstract Background This study set out to look at how naringenin affected the pharmacokinetics of ranolazine in rats. The pharmacokinetic investigation of ranolazine in rats following oral administration of ranolazine with or without coadministration of naringenin was successfully conducted using the established technique. Animals were administered the same medications for 7 days as part of a multiple dosage study (MDS), and the amount of ranolazine in plasma was calculated on 18 days. The intestinal transit of ranolazine in the presence and absence of naringenin and verapamil was examined in an in vitro experiment using the intestinal sacs of rats and chickens (P-glycoprotein inhibitor). Results Naringenin raised the maximal level (Cmax) of ranolazine from 231 ± 10.16 to 303.67 ± 9.46 and 325.67 ± 21.81 ng/mL in SDS and MDS, respectively. Moreover, naringenin elevated the area under the curve (AUC) of ranolazine from 1293.54 ± 37.18 to 1505.38 ± 100.30 and 1575.42 ± 76.98 ng/mL/h in SDS and MDS. In the presence of naringenin, there was an increase in the transfer of ranolazine from the mucosal side to the serosal side. Naringenin inhibits the enzymes Cytochrome P450 (3A4) or (CYP3A4) and P-glycoprotein (P-gp). The findings showed that naringenin might have a considerable impact on ranolazine pharmacokinetics, including extending its t1/2 and raising its AUC. Conclusions The findings of the study showed that naringenin inhibits the enzymes CYP3A4 and P-gp. Therefore, naringenin might have a considerable impact on ranolazine pharmacokinetics, including extending its t1/2 and raising its AUC. Graphical abstract